The Little Data Book on Climate Change 2011 - World Bank (World Bank, 2012)
The little data book on climate change includes a diverse set of indicators selected from the global economic and scientific communities. These indicators recognize the intrinsic relationship between climate change and development and attempt to synthesize important aspects of current and projected climate conditions, exposure to climate impacts, resilience, greenhouse gas emissions, and the current state of efforts to take action. The little data book on climate change draws upon several online resources, including the open data website, the climate change knowledge portal, and the open data for resilience initiative. These resources from the World Bank and the Global Facility for Disaster Reduction and Recovery (GFDRR) provide free and open access to data and information relevant to climate risk, climate change, and development at the international, national and subnational levels. These resources contain many more indicators than are available in the limited space of this book and include interactive tools, visualizations on the use and interpretation of the data. In addition, there are other tools that will help users and programmers access World Bank data and develop applications.